História em quadrinhos: uma proposta de ensino da língua portuguesa para surdo - Freitas, Mercia Cristina de Araíjo (2016)
This qualitative research aims to build an intervention proposal for the development of writing skills with deaf student. Thus we conducted a study on the teaching and learning process of the Portuguese language, bringing some reflections on the appropriate methodology to do so with some issues surrounding the learning of a second language for deaf students in the school context. We believe that the Brazilian Sign Language - Libras should guide the learning Portuguese as a second language in the written form for the Deaf. Therefore, the work was based on authors of studies on the learning of writing as a second language for the deaf (Lodi, 2013; Fernandes, 1999; Faria, 2012; Skliar, 1997; Quadros, 1997.1999, 2011, 2012; Quadros ; Schimedt, 2006; Paperback, 2003; and others), genre (Bakhtin, 1986, 1997; Marcushi, 2002; 2008; Elias; Koch, 2012, 2014; Dolz, Noverraz; Schineuwly, 2004), genre Comic (Mendonça, 2010; Rama, 2014; Ramos, 2014 Vilela, 2014; Vergueiro, 2014) and Teaching Sequence (Dolz; Noverraz; Schineuwly, 2004) .The methodology applied a Teaching Sequence as an intervention measure, which developed activities written with the genre Comic Monica's Gang. These activities that were carried out in five stages: presentation of the situation, the initial production, the development of modules, the rewriting of the initial production and production of a comic book. The methodology was developed in Basic Education School Paulista / PE city, in a class of 5th year with a deaf student included. For data collection selected initial production, the rewriting of this initial production and written production of a comic book with the elements of the genre. We recognize the end of this research through the narrative of comics you can build appropriate teaching strategies for learning Portuguese as a second language for deaf.